2007
DOI: 10.1007/s11120-007-9277-7
|View full text |Cite
|
Sign up to set email alerts
|

Relative binding affinities of chlorophylls in peridinin–chlorophyll–protein reconstituted with heterochlorophyllous mixtures

Abstract: Peridinin-chlorophyll-protein (PCP), containing differently absorbing chlorophyll derivatives, are good models with which to study energy transfer among monomeric chlorophylls (Chls) by both bulk and single-molecule spectroscopy. They can be obtained by reconstituting the N-terminal domain of the protein (N-PCP) with peridinin and chlorophyll mixtures. Upon dimerization of these "half-mers", homo- and heterochlorophyllous complexes are generated, that correspond structurally to monomeric protomers of native PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Polivka et al observed a stochiometric ratio of 1:2 for Chl‐ a :BChl‐ a integration into RFPCP refolded with a 1:1 mixture of the Chls [20]. This observation is confirmed by the biochemical quantification experiments of Brotosudarmo et al who found that acChl‐ a (difference between BChl‐ a and acChl‐ a is the saturation of C7–C8 bond) is integrated twice as often as Chl‐ a [21] . Again, Brotosodarmu et al proposed an H‐bond to account for the observed preference for acChl‐ a over Chl‐ a .…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Polivka et al observed a stochiometric ratio of 1:2 for Chl‐ a :BChl‐ a integration into RFPCP refolded with a 1:1 mixture of the Chls [20]. This observation is confirmed by the biochemical quantification experiments of Brotosudarmo et al who found that acChl‐ a (difference between BChl‐ a and acChl‐ a is the saturation of C7–C8 bond) is integrated twice as often as Chl‐ a [21] . Again, Brotosodarmu et al proposed an H‐bond to account for the observed preference for acChl‐ a over Chl‐ a .…”
Section: Resultsmentioning
confidence: 81%
“…Brotosudarmo et al have observed a higher binding affinity for Chl‐ b over Chl‐ a in RFPCP in single molecule spectroscopic studies [19] which was confirmed in biochemical quantification experiments [21]. Based on a structural alignment of Chl‐ b onto Chl‐ a , they proposed a hydrogen bond between the formyl group and the C1′‐hydroxyl group of Per‐612 to account for the higher affinity.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The peridinin–chlorophyll–protein complexes used in our experiments were prepared as described [16]. In order to obtain PCP complexes containing Chl, the N-terminal apoprotein was reconstituted with an appropriate mixture of Per and, as desired, Chl or acChl.…”
Section: Samples and Experimentsmentioning
confidence: 99%
“…The absorption (and fluorescence excitation) spectrum of the acChl–PCP has an intense, broad band between 400 and 550 nm that is due to Per and two Chl bands at 440 nm (Soret) and 690 nm (Q Y ), the emission spectrum peaks at 690 nm (Fig. 1a) [16].
Fig.
…”
Section: Samples and Experimentsmentioning
confidence: 99%